Efektivitas Pemberdayaan Masyarakat Dalam Pengembangan Kampoeng Batik Jetis - Ima Nur Rosyida; Hasan Ismail (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The construction in a country essentially to give the welfare live of society. The current growth in Indonesia has been achieved by one of the batik industrialization sectors. Batik becomes an industrial potential that can be developed as an form of creative economic growth and thus become a village development community empowerment activity. This inscription to know how effectively empowering societies are in rural development, especially in development at Kampoeng Batik Jetis. This study uses qualitative descriptive analysis method. The result indicated that the empowerment of communities taken are as follows 1) Skill, encompass education and training; 2) Market access, accessibility acquire raw materials and other supporting materials in improving the production processes, implicate UMKM exhibition to expand market access, and facilitate intellectual property rights; 3) Capital access, comprise capital facilitate.